Teaching Wudu through Movement and Songs: Enhancing Early Childhood Engagement in Islamic Learning - Ika Puspita Sari; Nur Fadillah Minda; Hapsa Humairah; Fadhilah Azzahra; Sahraeni; Ica Ica (Journal of Indonesian Islamic Studies, 2024)
Teaching Islamic ritual practices to young children requires instructional approaches that are developmentally appropriate, engaging, and meaningful. Among the fundamental religious practices introduced in early childhood Islamic education, wudu plays an essential role as a prerequisite for prayer and as an important component of children’s spiritual development. However, teaching wudu to young learners can be challenging when instructional methods rely primarily on verbal explanations and memorization. This study aims to explore the implementation of movement and song methods in teaching wudu to children and to examine their contribution to children’s engagement in Islamic learning. Employing a qualitative descriptive research design, the study was conducted at Umega Kindergarten, Palopo City, Indonesia. Data were collected through classroom observations, semi-structured interviews, and document analysis and were analyzed using an interactive qualitative analysis model. The findings reveal that the movement and song method was implemented through a combination of musical activities, physical demonstrations, and guided practice that enabled children to learn wudu procedures in an interactive and enjoyable manner. The method significantly enhanced children’s engagement, as reflected in their enthusiasm, active participation, sustained attention, confidence, and ability to remember the sequence of wudu practices. The study also identified several supporting factors, including children’s interest in music and movement, teacher creativity, and a supportive learning environment, as well as challenges related to time constraints and differences in learning abilities. This study contributes to the field of early childhood Islamic education by demonstrating that movement and songs can function as an effective child-centered pedagogical approach for strengthening engagement and facilitating the learning of Islamic ritual practices among young children.